2022
DOI: 10.1111/jcmm.17529
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in tumor immunity and therapy

Abstract: Ferroptosis is a newly discovered oxidative cell death triggered by excessive iron-mediated lipid peroxidation. 1,2 It was first reported in 2012 when it was found that some small molecules (e.g., erastin and RSL3) could specifically induce a non-apoptotic form of RCD in cancer cells; this RCD could be blocked by lipophilic antioxidants or iron chelators (e.g., vitamin E and ferrostatin-1). 3 The morphological characteristics of ferroptotic cells are different from those of apoptotic cells. Apoptotic cells are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 164 publications
(379 reference statements)
0
12
0
Order By: Relevance
“…It has been reported that ferroptosis is strictly correlated with the tumor immune microenvironment [56][57][58][59][60]. Weimin Wang et al [61] explored that activating CD8+ T cell increases particular lipid peroxidation in tumor cells, facilitating the process of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ferroptosis is strictly correlated with the tumor immune microenvironment [56][57][58][59][60]. Weimin Wang et al [61] explored that activating CD8+ T cell increases particular lipid peroxidation in tumor cells, facilitating the process of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A mounting number of studies have reported that macrophages in the TME can undergo reception and integration of signals from the environment, communicate at the cell‐to‐cell level and successfully interconvert between different polarization states. 93 Following this, macrophages of different polarization types remodel the tumour immune microenvironment from different perspectives. Iron‐dead tumour cells release oxidized lipids, eicosanoids (5‐HETE, 11‐HETE and 15‐HETE), prostaglandins (PEG) and DAMPs as signalling messengers interacting with other components in the TME.…”
Section: Non‐apoptotic Rcd Mediates Time...mentioning
confidence: 99%
“…A mounting number of studies have reported that macrophages in the TME can undergo reception and integration of signals from the environment, communicate at the cell‐to‐cell level and successfully interconvert between different polarization states 93 . Following this, macrophages of different polarization types remodel the tumour immune microenvironment from different perspectives.…”
Section: Non‐apoptotic Rcd Mediates Time Reprogramming Of Macrophagesmentioning
confidence: 99%
“…According to their original study, comparing this iron-dependent cell death to other forms of RCD reveals distinct morphological, biochemical, and genetic differences [ 43 ]. The morphology of ferroptotic cells is characterized by smaller mitochondria, increased mitochondrial membrane density, decreased or absent cristae, outer mitochondrial membrane rupture, and the nuclei are normal in size without chromatin aggregation [ 44 ]. Accumulating studies have demonstrated that ferroptosis plays a crucial role in the development and progression of various diseases, including neurological disorders [ 45 ], cardiovascular diseases [ 46 ], ischemia-reperfusion injury [ 47 ], and cancer [ 48 ].…”
Section: Regulated Cell Death and Ferroptosismentioning
confidence: 99%